Adolescent and covert family planning users' experiences self-injecting contraception in Uganda and Malawi: implications for waste disposal of subcutaneous depot medroxyprogesterone acetate - Holly M. Burke; Catherine Packer; Laura Wando; Symon Peter Wandiembe; Nelson Muwereza; Subarna Pradhan; Akuzike Zingani; Bagrey Ngwira (BMC, 2020)
Abstract Background Self-administered subcutaneous depot medroxyprogesterone acetate (DMPA-SC) is poised to increase access to contraception; however, governments are concerned about the waste management of used units. Self-injectors in Malawi and Uganda are currently instructed to store used units in containers and return them to health workers for disposal. However, this may not be feasible in low-resource settings, especially for younger or covert self-injectors. We describe adolescent (15-19 years) and adult (20-49 years) self-injectors' disposal experiences in Uganda and Malawi. When possible, we compare covert and overt users' experiences. Methods We conducted cross-sectional qualitative studies in 2019 with 50 self-injectors in Uganda and 60 in Malawi. We purposively selected approximately half adolescents and included those trained by clinic-based providers and community health workers. We conducted semi-structured interviews and thematic data analysis and compared the findings across settings. Results Just under half of both samples were adolescents, substantially more of whom were covert users in Uganda (68%) than Malawi (~ 10%). Most participants reported being told to store used units in a container and return them to health workers. About two-thirds of Uganda participants had disposed of at least one unit by the interview, most commonly returning them to health workers. Over one-third of Malawi participants had disposed of at least one unit by the interview, slightly more disposed into latrines compared to returning to health workers. Participants in both settings reported compliance with health workers' disposal instructions as a primary reason for their disposal method. One-fifth of Uganda participants, mostly adolescent covert users, and one-quarter in Malawi said they were told they could dispose into latrines, and often did so. The majority in both settings said they would prefer to dispose units in latrines because they worried about needlestick injuries to others and because it was convenient. Some Uganda adolescent covert users felt returning units to health workers was challenging due to privacy concerns. Conclusions While most self-injectors disposed of used units as instructed, findings from both studies suggest that returning units to health workers is not preferred and may not be feasible for some adolescent covert users. More convenient disposal solutions should be identified.